Reunification of looked‐after children with their birth parents in the United Kingdom: A literature review and thematic synthesis. Issue 1 (27th June 2019) - Carlson, Lyndsey; Hutton, Stephanie; Priest, Helena; Melia, Yvonne
Abstract: Background: Reunification of looked‐after children with their birth parents is the most common route to permanency for looked‐after children in the United Kingdom. Previous research evidence, mainly from American studies, suggests numerous factors that contribute to successful reunification outcomes (Biehal, 2007). Less is known about the current evidence base for reunification practice in the United Kingdom. Objective: This review aimed to identify, appraise, and synthesize published literature concerned with the reunification of looked‐after children with their birth parents in the United Kingdom. Methods: A systematic search of the literature identified eight peer‐reviewed studies conducted between 2005 and 2017 exploring reunification practice in the United Kingdom. Studies were critically appraised and thematically synthesized according to the Thomas and Harden (2008) approach. Results: Eight articles met eligibility criteria. Descriptive themes were support, case management, oscillation, parenting, and reoccurrence of abuse. Analytic themes were lack of guidance and risks associated with return. Conclusions: A pattern of oscillation between home and care was common for many looked‐after children, and remaining in care produced relatively better outcomes. Difficulties arise when comparing studies on reunification, due to methodological variation. Further research is needed to explore the views of reunited children themselves.